2008
DOI: 10.1093/bja/aen203
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the perioperative management of adult patients with chronic kidney disease

Abstract: The complications of chronic kidney disease (CKD) present the anaesthetist with a number of clinical challenges related in part to altered drug handling and to difficulties with vascular access and fluid balance. Safe anaesthetic management requires an understanding of CKD pathophysiology to prevent aggravation of pre-existing disease. This review will consider some recent changes in the management of adult patients with CKD as they affect the anaesthetist. It will consider medical problems associated with CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 137 publications
(120 reference statements)
2
46
0
3
Order By: Relevance
“…This places them at a higher perioperative risk of opioid-induced respiratory depression, necessitating consideration of opioid-reducing strategies such as early fracture fixation, regular simple analgesia (but not non-steroidal anti-inflammatory drugs [7,22]) and regional nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
“…This places them at a higher perioperative risk of opioid-induced respiratory depression, necessitating consideration of opioid-reducing strategies such as early fracture fixation, regular simple analgesia (but not non-steroidal anti-inflammatory drugs [7,22]) and regional nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
“…As in primary hyperparathyroidism [8], hyperparathyroidism secondary to chronic kidney failure may be related to the prothrombotic thromboelastographic profile presented. While the traditional concern of anesthesiologists and surgeons during surgery on patients with chronic kidney failure is the possibility of greater surgical bleeding [9], clinical evidence has demonstrated that chronic kidney disease is also associated with blood clotting abnormalities that favor a pro-thrombotic hypercoagulable state [3][4][5]10], with an increased risk of thromboembolic phenomena that may increase with the decline in kidney function [3]. While the risk of bleeding may be due to uremia (abnormal platelet function) and anemia (alteration from normal flow in blood vessels) [3,5,9], the tendency toward hypercoagulability likely also has a multifactor nature (increased levels of pro-coagulation factors, reductions in endogenous anticoagulants and fibrinolytic activity and the use of erythropoietin) [3].…”
Section: Discussionmentioning
confidence: 99%
“…While patients with chronic kidney failure are traditionally considered to be at risk for perioperative bleeding due to the platelet dysfunction related to uremia, anemia and frequent dialysis [2,3], clotting disorders that favor a hypercoagulable state have also been demonstrated in such patients [2,4,5]. Therefore, the perioperative management of patients with chronic kidney failure is a huge challenge due to both the hypercoagulable state and increased risk of bleeding.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…при Тэкс и ТэТс в подобных случаях использу-ется как цементная, так и бесцементная фикса-ция эндопротезов. для пациентов на гемодиа-лизе, по данным многочисленных исследований, характерны большая длительность госпитализа-ции, больший процент сердечно-сосудистых, не-врологических, тромботических, инфекционных, геморрагических и других общетерапевтических осложнений, в совокупности приводящих к боль-шей летальности по сравнению с популяцией без ХБп [24][25][26]. сообщается также о существенно большей частоте таких хирургических осложне-ний, как перипротезная инфекция и переломы, расшатывание компонентов эндопротезов и не-обходимость ревизий.…”
unclassified